TREE SPECIES SUSCEPTIBILITY TO LEAF-CUTTING ANTS ATTACK IN CARBON NEUTRALIZATION PLANTATIONS (Nativa, 2021)
ABSTRACT: Greenhouse gas (GHG) emissions neutralize planting are one of the options for climate changes mitigating. Leaf-cutter ants attack is a threat to the plantations proper development. Ants have selective foraging, which makes it important to know this selectivity and, thus, choose more suitable species to neutralization planting compose. Thus, the goal of the present study was to evaluate the tree species susceptibility to be attacked by leaf-cutter ants in carbon neutralization plantations. The study was carried out in mixed plantations in Viçosa-MG and a classification was created for the present species. The Damage Index (DI) was created by multiplying the Mean of Severity (MS) and the Frequency of Attacks (FA). The species were classified according to the indication for neutralization plantations (indicated, moderately indicated, and not indicated) and potential species for the extraction of natural insecticides. From the 59 species evaluated, 22 were classified as suitable for neutralization plantations, 6 as moderately indicated, 24 as not indicated, and 7 as potential species for extracting natural insecticides.Keywords: forest carbon; pest control; carbon offset; mixed plantings. Susceptibilidade de espécies arbóreas ao ataque de formigas cortadeiras em plantações de neutralização de carbono RESUMO: O plantio para neutralizar as emissões de gases de efeito estufa (GEE) é uma das opções para mitigar as mudanças climáticas. O ataque de formigas cortadeiras é uma ameaça ao bom desenvolvimento dessas plantações. As formigas possuem forrageamento seletivo, o que torna importante conhecer essa seletividade e, assim, escolher espécies mais adequadas para compor o plantio de neutralização. Assim, o objetivo do presente estudo foi avaliar a susceptibilidade de espécies arbóreas ao ataque de formigas cortadeiras em plantios de neutralização de carbono. O estudo foi realizado em plantios mistos do programa Carbono Zero em Viçosa-MG e, com base nessa avaliação, foi criada uma classificação para as espécies presentes. O Índice de Danos (DI) foi criado pela multiplicação da Média de Severidade (MS) e da Frequência de Ataques (FA). As espécies foram classificadas quanto à indicação para plantios de neutralização (indicada, moderadamente indicada e não indicada) e espécies potenciais para extração de inseticidas naturais. Das 59 espécies avaliadas, 22 foram classificadas como aptas para plantios de neutralização, 6 como moderadamente indicadas, 24 como não indicadas e 7 como espécies potenciais para extração de inseticidas naturais.Palavras-chave: carbono florestal; controle de pragas; compensação de carbono; plantios mistos.